Cognitive outcomes after acute coronary syndrome: a population based comparison with transient ischaemic attack and minor stroke. - Volonghi, I; Pendlebury, S; Welch, S; Mehta, Z; Rothwell, P (2013)
OBJECTIVE: Acute coronary syndrome (ACS) is associated with increased risk of cognitive decline when compared with controls, but case:control studies are subject to selection bias. We therefore compared cognitive outcomes in ACS with transient ischaemic attack (TIA) and minor stroke, diseases with similar risk factor burden generally considered to be at high risk of cognitive decline. DESIGN: Prospective population based cohort study SETTING: Oxford Vascular Study (OXVASC) carried out within a defined population of 91 000 in Oxfordshire, UK. PATIENTS: 614 in total: 216 ACS, 182 TIA, 216 minor (non-disabling) stroke. OUTCOME MEASURES: Mini-Mental-State-Examination (MMSE), Telephone Interview for Cognitive Status-modified (TICSm), and Montreal Cognitive Assessment (MoCA) at 1 and 5 years. RESULTS: Overall risk factor burden was similar across groups but ACS patients had more smoking (27% vs 14%, p<0.001) and less hypertension (45% vs 53%, p<0.01) and atrial fibrillation (6% vs 14%, p<0.001). Cognitive outcomes were worse at 1 year in ACS versus TIA patients: mean±SD MMSE 26.6±2.7 vs 27.6±2.5, p<0.0001; OR=2.14, 95% CI 1.11 to 4.13 for moderate/severe cognitive impairment (MMSE <24) with a similar trend at 5 years, and ACS outcomes were more similar to minor stroke. Memory and language versus frontal/executive subtests were relatively more impaired in ACS than TIA and minor stroke patients. CONCLUSIONS: Risk of cognitive impairment after ACS is similar to minor stroke and higher than TIA with implications for clinical practice including consent and adherence with medication. Differences in cognitive domain performance suggest a greater role for degenerative brain pathology in ACS which may be linked to vascular risk profile and cardiac factors.